Chapter 13 The Roles of 'Old' and 'New' Media Tools and Technologies in the Facilitation of Violent Extremism and Terrorism - Scrivens, Ryan (Taylor & Francis, 2019)
This chapter describes and discusses the roles of media tools and technologies in the facilitation of violent extremism and terrorism. Rather than focusing on how media report on terrorism, we investigate how extremist and terrorist groups and movements themselves have exploited various "traditional" and "new" media tools, from print to digital, outlining the significance that they have had on extremists' ability to mark territory, intimidate some audiences, connect with other (sympathetic) audiences, radicalize, and even recruit. Underlined is that violent extremists and terrorists of all stripes have, over time, used every means at their disposal to forward their communicative goals. Also worth noting is that 'old' media tools are not extinct and while 'new' media play a prominent role in contemporary violent extremism and terrorism, 'old' tools-everything from murals to magazines-continue to be utilized in tandem with the former.